Deflazacort and Prednisolone in the Treatment of Initial Episode of Idiopathic Nephrotic Syndrome in Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Prednisolone is the 1st choice of drug in Idiopathic Nephrotic Syndrome (INS). Deflazacort (DFZ) is a new step in this regard. Aim of this study was to compare the efficacy of prednisolone and DFZ in children with INS. Materials and methods: 76 children of 2-16 years with INS were enrolled in a Randomized Controlled Trial (RCT). Patients were randomized to either group-A (DFZ) or group-B (Prednisolone) and 38 children were allocated in each groups. After giving treatment with both drugs, these patients were followed up at 3 months interval for 2 times to compare the clinical effects. Due to lost follow up finally 65 patients were analyzed. Data was documented on pre-structured data sheet and analyzed by SPSS version 22.0. Chi square test for categorical data and unpaired ttest for continuous data were done. A probability (p) value < 0.05 was considered statistically significant. Results: Mean time to get remission was 5.32±1.28 days in DFZ group and 8.00±2.55 days in prednisolone group. It was statistical significant (p=